Social Milieus and Social Integration. From Theoretical Considerations to an Empirical Model - Olaf Groh-Samberg; Tim Schröder; Anne Speer (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Current debates on threats to social integration in times of multiple crises call for a~better understanding of the relationship between socioeconomic inequality and sociocultural value conflicts. The aim of this article is to (re)introduce the concept of social milieus as a~promising approach to capture the complexity of this relationship at the group level. We offer a~theoretical extension of the concept of social milieus, which has so far been limited to the German discourse, by linking it to the international debate on sociocultural "cleavages" and cultural value conflicts. Social milieus are defined as large latent groups with similar socioeconomic positions and cultural values. Accordingly, they develop milieu-specific forms of social integration in potentially conflictual demarcation from other milieus. This conceptualization offers a~theoretical framework for analyzing social integration from the perspective of social groups in terms of social integration within social milieus and relationships between milieus. In order to illustrate the capabilities of this theoretical approach, we develop a~first empirical model of social milieus in Germany based on a~Latent Class Analysis of socioeconomic indicators and Schwartz' basic human values. With this theoretical concept and empirical model, we put social milieus on the international research agenda for the analysis of social integration within and between social groups.
Keywords: 300; Basic human values; Socioeconomic status; Stratification; Sociocultural cleavages; Latent Class Analysis; Allgemeine menschliche Werte; Sozioökonomischer Status; Stratifikation; Soziokulturelle Spaltungen; Latente Klassenanalyse